Palinología y sedimentología de la Formación Melo (Pérmico) en la cañada "El Barón", departamento de Cerro Largo, Uruguay (Ameghiniana, 2014)
A palynological analysis of one surface sample of black shale from the "El Barón" stream, Cerro Largo, Uruguay, was performed. Twenty one species were found, corresponding to 16 genera. The assemblage is almost exclusively composed of striated pollen grains. The most frequent genera are: Vittatina, Weylandites, Marsupipollenites, Lunatisporites and Lueckisporites. This assemblage was compared with others from the same basin using principal components analysis (PCA). The results of this analysis indica te that the El Barón palynological assemblage is very similar to that found in borehole 221 (Cerrillada) and is rather different from the rest of the palynoflorae described from the Melo Formation. From the biostratigraphical point of view, this palynoflora is comparable with the Lueckieporites virkkiae Biozone from the Paraná basin in Brazil and with the Striatites Biozone from the Chaco-Paraná basin in Argentina, which is interpreted as Late Permian in age. It is inferred that arid environmental conditions prevailed at the moment of the deposition of the studied sediments.